The effects of state aid on Total Factor Productivit growth - Patrick Van Cayseele; Jozef Konings; Ilona Sergant (National Bank of Belgium, 2014)
This paper analyzes the relationship between state aid and ?rm performance in terms of productivity growth. To this end, we use all European state aid cases that were granted (either to an individual ?rm or a group of ?rms under the form of a scheme) in manufacturing between 2003 and 2011. Our ?ndings show that state aid measures are able to enhance productivity growth when ?rms are constraint due to a lack of cash availability. Since laggard ?rms are more likely to be ?nancially constraint, they experience more TFP growth than ?close-to-frontier??rms when receiving state aid. This bene?cial eect of state aid is mainly driven by the post-crisis years in the sample. Our results are consistent with optimal development planning by pro?t maximizing ?rms.
Keywords: 330; Subvention; Wirkungsanalyse; Produktivitätsentwicklung